2022
DOI: 10.1089/dna.2021.1034
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA LINC00963 Inhibits Corneal Fibrosis Scar Formation by Targeting miR-143-3p

Abstract: Corneal fibrosis is a complication of severe corneal injury, one of the major causes of vision loss. The formation of myofibroblasts has emerged as a key stimulative factor of corneal fibrosis. In the current study, we focused on the role of LINC00963 in regulating corneal fibrosis. Transforming growth factor β1 (TGF-β1) was used to induce human corneal stromal cells differentiating into corneal myofibroblasts, and the significant increase of α-smooth muscle actin (α-SMA) was verified by quantitative real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…3 A). One of the previous studies has shown that MetaLnc9 regulated the TGF-β1-induced myofibroblast transdifferentiation of corneal fibroblasts by sponging miR-143-3p, 12 which also mediates subconjunctival fibrosis. 17 Hence, we examined whether MetaLnc9 physically interacted with miR-143.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A). One of the previous studies has shown that MetaLnc9 regulated the TGF-β1-induced myofibroblast transdifferentiation of corneal fibroblasts by sponging miR-143-3p, 12 which also mediates subconjunctival fibrosis. 17 Hence, we examined whether MetaLnc9 physically interacted with miR-143.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, it has been revealed that MetaLnc9 inhibits the TGF-β1-elicited myofibroblast transdifferentiation of corneal fibroblasts as well as lowers the secretion of collagen I and III by downregulating miR-143-3p. 12 As such, it is intriguing to inspect whether MetaLnc9 is pro-fibrosis or anti-fibrosis during myofibroblast transdifferentiation of BMFs and associated molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs were suggested as potential biomarkers of different diseases, including certain corneal diseases, and were also proposed as possible treatment targets [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…EMT is one of the key embryological mechanisms, and involves epithelial cells losing their polarity and obtaining mesenchymal properties. EMT also participates in tissue repair; inflammation; fibrosis, including fibrosis of the cornea after trauma or infection; and tumor metastasis [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, miR-205 promotes the spread of epithelial cells to the site of corneal damage upregulating the AKT- and F-actin-mediated pathways [ 110 ] and inhibiting the KCNJ10 channel [ 111 ]. Moreover, miRNA-143-3p inhibition downregulates the expression of α-SMA, thereby reducing contractility of myofibroblasts and thus the tissue fibrotic response [ 112 ]. MiRNA-200a also inhibits fibrosis blocking corneal epithelial cell migration [ 113 ].…”
Section: Subcellular Therapiesmentioning
confidence: 99%